2020
DOI: 10.11113/jt.v82.13354
|View full text |Cite
|
Sign up to set email alerts
|

Performance Features of the Sunflower Seeds Oil as a Hydraulic Bio Fluid Under Various Normal Loads

Abstract: Plant (vegetable) oils are renewable fluids. They have been developed to replace mineral-based fluids. Due to their distinguished features including eco-friendly properties and possibility of reducing the hydrocarbon and carbon dioxide emission when being used in the industrial processes or internal combustion (IC) engines, they are considered a sustainable source of biodegradable fluids. In this work, non-edible sunflower oil is investigated as a bio hydraulic fluid under various normal loads utilizing the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, the sample fluid will be heating up to 75°C and this experiment is going to run in 60 minutes. Table 1 shows the specifications of balls that been used in this study [33]. Other that Fourball Tribotester, 3D Surface Measurement System (Alicona) with the usage of the optic IFM G4 10x have also been used in this research in order to measure the wear scar diameter that is being produced at the three balls at the bottom.…”
Section: Methodology 21 Apparatus and Proceduresmentioning
confidence: 99%

Tribological Characterisation of Biofluid Using Four Ball Experiment

M. Mazwan Mahat,
Farah Nabillah Kazwa,
Nurul Nadiah Mohd Kamaldin
et al. 2024
AREFMHT
“…In addition, the sample fluid will be heating up to 75°C and this experiment is going to run in 60 minutes. Table 1 shows the specifications of balls that been used in this study [33]. Other that Fourball Tribotester, 3D Surface Measurement System (Alicona) with the usage of the optic IFM G4 10x have also been used in this research in order to measure the wear scar diameter that is being produced at the three balls at the bottom.…”
Section: Methodology 21 Apparatus and Proceduresmentioning
confidence: 99%

Tribological Characterisation of Biofluid Using Four Ball Experiment

M. Mazwan Mahat,
Farah Nabillah Kazwa,
Nurul Nadiah Mohd Kamaldin
et al. 2024
AREFMHT
“…From the two Figures 5 and 6 could be observed that the values of the friction coefficient began decreasing gradually over time and also noted that the values of friction coefficient of vegetable fluids are lower at high load as in the case of normal load 20 kg., which was 0.0159 and 0.0230 for the corn and mineral fluid respectively, this result can be attributed to the long chain fatty acid and the esters which are known as active anti-friction materials [18][19][20][21][22][23][24][25].…”
Section: Coefficients Of Frictionsmentioning
confidence: 99%